1999
DOI: 10.1159/000024961
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Unenveloped DNA Virus (TT Virus) Associated with Acute and Chronic Non-A to G Hepatitis

Abstract: In 1997, a novel DNA virus was isolated from the serum of a patient with posttransfusion hepatitis of unknown etiology in Japan, and it was named TT virus (TTV) after the initials of the index patient. TTV is a nonenveloped, single-stranded and circular DNA virus, and its entire sequence of ∼3.9 kb has been determined. For being a DNA virus, TTV has a wide range of sequence divergence, allowing the classification into at least 16 genotypes separated by a sequence difference of >30% from one another. The nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 29 publications
(56 reference statements)
0
40
1
2
Order By: Relevance
“…Since the first isolation of TTV, most studies have shown that it might be relevant to liver disorders and liver damage and have a possible association with fulminant hepatitis, cryptogenic liver disease, non-A-G hepatitis, posttransfusion hepatitis, liver cirrhosis, and hepatocellular carcinoma (11,22,37,41,57,65). At the same time, epidemiological associations of TTV with B-cell lymphoma, Hodgkin's disease, aplastic anemia, idiopathic pulmonary fibrosis, acute respiratory disease, and autoimmune rheumatic disorders have also been described (6,16,29,30,32,52).…”
mentioning
confidence: 99%
“…Since the first isolation of TTV, most studies have shown that it might be relevant to liver disorders and liver damage and have a possible association with fulminant hepatitis, cryptogenic liver disease, non-A-G hepatitis, posttransfusion hepatitis, liver cirrhosis, and hepatocellular carcinoma (11,22,37,41,57,65). At the same time, epidemiological associations of TTV with B-cell lymphoma, Hodgkin's disease, aplastic anemia, idiopathic pulmonary fibrosis, acute respiratory disease, and autoimmune rheumatic disorders have also been described (6,16,29,30,32,52).…”
mentioning
confidence: 99%
“…TTV is thought to be a new member of the Circoviridae family of viruses, and it was recently proposed that the virus be named Torque Teno virus (6). The TTV genome includes an untranslated region (UTR) of approximately 1.2 kb and a coding region of approximately 2.6 kb, including two major open reading frames which are sandwiched by the TATA box and polyadenylation signal motifs (11,13,15). Analyses of TTV transcripts have revealed three spliced mRNA species of 3.0, 1.2, and 1.0 kb with common 5Ј and 3Ј termini (9,14).…”
mentioning
confidence: 99%
“…1A). Despite considerable genetic diversity throughout the whole genome, the UTR sequence was relatively conserved among the different TTV genotypes, presumably reflecting its functional constraints (15,16). Thus, we analyzed transcriptional regulation of the UTR sequence.…”
mentioning
confidence: 99%
“…Такая распространенность вируса может объясняться различными механизма-ми передачи вируса: естественным при контактном механизме, реализующимся половым путем и во время родов, а также искусственным -при различ-ных медицинских и немедицинских манипуляциях. В работах некоторых исследователей доказана гепа-тотропность ТТ вируса с развитием клиники остро-го и хронического гепатита [19,28,39]. Изучение микст-инфекции ТТV и НСV показало, что такая коморбидность способствует более быстрому про-гресированию гепатита в цирроз печени [34].…”
Section: эпидемиология Ttv-инфекцииunclassified
“…Обнаружение TTV DNA в желчи и совпадение ха-рактеристик этих изолятов вируса с частицами TTV, выделенными из крови и фекалий, позволяет, по аналогии с гепатитами А и Е, утверждать, что TTV размножается в гепатоцитах, откуда поступает в желчные протоки, с желчью попадает в кишечник и далее -в фекалии [28]. Так как TTV не имеет ли-пидной оболочки, его патогенность и вирулентность не снижается под воздействием желчных кислот, растворяющих липидную оболочку других вирусов.…”
Section: эпидемиология Ttv-инфекцииunclassified